Work related injuries and musculoskeletal disorders among child workers in the brick kilns of Nepal - Sunil Kumar Joshi; Pranab Dahal; Agya Poudel; Helen Sherpa (Occupational Health and Safety Society of Nepal, 2014)
Brick manufacturing is a labor intensive informal industry using child workers as the major work force in Nepal. Workers are required to use physical strength, carry heavy loads and remain in a squatted posture for longer periods doing repetitive tasks posing threats to musculoskeletal system. This study involved cross sectional study of children aged 17 years and below. The study respondent included 101 cases and 64 controls in Bhaktapur and 97 cases and 43 controls in Sarlahi. Lack of adequate physical infrastructures, poor working conditions with non existent safety procedures have posed risk to physical, metal and overall well being of children. The study identifies work related physical ailments and discomforts dominate brick industries of Nepal. The musculoskeletal disorder related pain and discomfort was experienced by 73 per cent of working children in Bhaktapur and 58 per cent in Sarlahi. The odds ratio suggests that working children were 8 times more likely to experience trouble or body pain compared to non-working children. This study finds that presence of inferior physical environment, working conditions and practices has contributed to musculoskeletal injuries and problems exposing working children to risks and hazards